Proteinase 3 associated with Wegener's granulomatosis - Goldmann, Wolfgang (Cell Biology International, 2022)
Wegener's granulomatosis (WG) is a form of systemic vasculitis characterized by granulomatous inflammation of the upper and lower airways, vasculitis, and necrotizing glomerulonephritis. It is strongly associated with anti-neutrophil cytoplasmic antibodies against proteinase 3 (PR3-ANCAs). Various in vitro observations provided strong evidence that autoimmune PR3-ANCAs are directly involved in glomerular and vascular inflammation. However, little is known about the pathogenic significance of PR3-ANCAs in vivo. Therefore, the generation of animal models helped to validate the suggested autoimmune origin and pathophysiology in WG. To characterize and improve the models, numerous studies were carried out to elucidate the effect of mouse/rat PR3-ANCAs on neutrophil function as well as the role of CD4/CD8 in T and B cells and antibodies in the pathogenesis of the disease. Understanding the pathogenesis is therefore critical to relate these models to human studies hoping that they will be useful for better insight of WG and the development of specific therapies for the disease.
CRIS-Team WoS Importer:2022-01-14